PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PENGGUNA JASA TRANSPORTASI GRABBIKE DI KELURAHAN BOJONGGEDE - Wawan Hari Subagyo; Dulloh Rafsanjani (Institut Teknologi dan Bisnis Dewantara, 2022)
This study aims to determine the effect of service quality and price on customer satisfaction using GrabBike transportation services in Bojonggede Village. In this study, the population is customers who use Grabbike online motorcycle taxi transportation services in Bojonggede Village because the number of population to be studied is not identified (unidentified), so in this paper the authors took a sample of 100 people/respondent. The results of the study show: (1) Service Quality and Price Variables have an effect on Customer Satisfaction. (2) The results of the F test or simultaneous obtained the value of Fcount = 15,468, greater than Ftable (2,385). So it can be concluded that the service quality and price variables together have an effect on GrabBike Customer Satisfaction in Bojonggede Village. (3) The most dominant variable affecting customer satisfaction is the service quality variable with the largest coefficient value of 0.323. (4) the result of the determination test is 0.226, which means that the contribution of the service quality and price variables to customer satisfaction is 22.6%. From this value, it means that the variables of Service Quality and Price affect customer satisfaction. While the remaining 77.4% is influenced by other factors that are not discussed in this study.